Human Resource Development Strategy in Medan City, North Sumatra - Hutapea, Jhoni Maslan (LifeSciFi, 2024)
The capability of the civil servant 's human resources is one of the keys to successful development. Efforts to develop the knowledge and work abilities of civil servant require a strategy to be able to support the vision and mission of development, including in the Medan City Government. This research aims to analyze the strategies implemented by the Medan City Regional Education and Training Personnel Agency in developing human resources within the Medan City Government. The research uses a descriptive method, which aims to describe the actual situation regarding human resource development in the Medan City Government environment, with data sourced from relevant references, documents related to the research object to be analyzed and evaluated which is then used as a conclusion . A literature review helps a writer know the history and nature of his subject and identify gaps in the research problem. The results of the research show that the Medan City regional education and training personnel agency has attempted to develop the civil servant within the Medan City Government with various strategies, including through, functional training, technical training, and being directed to attend seminars, workshops, internships, and take courses which can support the knowledge and work abilities of its employees, however there are still several obstacles and challenges in achieving success.